Plasticity and divergence in ultraviolet reflecting structures on Dogface butterfly wings - Fenner, Jennifer (Ventricular Restraint Improves Outcomes in HF Patients with CRT, 2019)
The vast diversity of animal coloration is generated through a combination of pigment and structural colors. These colors can greatly influence the fitness and life history of an organism. Butterflies and their wing colors are an excellent model to study how these colors can impact the development and success of an organism. In this study, we explore species differences in structurally-based ultraviolet coloration in the Zerene butterfly. We show clear species differences in ultraviolet (UV) pattern and reflectance spectra. By varying larval diet, we show evidence for developmental plasticity in the structure and organization of UV reflecting scales in Zerene cesonia. We further show that feeding the larval host plant of Zerene eurydice to Z. cesonia does not result in greater similarity in scale structure or UV coloration to the sister species. These results not only demonstrate a connection between plasticity in a male ornamentation, UV wing pattern, and larval resource acquisition, but also identify candidate structural and organizational changes in wing scales responsible for the trait variation.